Publicidade dirigida a criança: análise doutrinária e tendência jurisprudencial - Braga, Fernanda Soares (2017)
Advertising campaigns have used child behavior analysis to persuade this audience to acquire their products and identify with their brand. In addition to the dissemination of products and brands, some values are propagated by advertising, often incompatible with children's citizenship and health. The main objective of this dissertation is to identify the effects of advertising on children. Based on this element, it examines the protection granted to children and adolescents in Brazilian law, especially in the context of consumer law. Initially, it seeks to delimit the concept, classifications and principles that govern advertising: the negative influence of the media on the development of children and adolescents has been proven by several researches. Publicity directed to the infantile-juvenile public characterizes as abusive, by disrespecting its condition of subject of rights. As is known, children are still in the stage of physical and psychic development. Therefore, they do not possess the same mental awareness and understanding that adults have about reality. As a result, they are not in a position to confront, with discernment, the pressure exerted by advertising on the issue of consumption. It also seeks to evaluate if the rules of current legislation have been effective in protecting this segment of the population. This analysis was made from the presentation of a statistical diagnosis on the measures of control of the publicity taken by the organ of self-regulation. Finally, an empirical analysis of the judgments carried out by the Judiciary was carried out. After this analysis is presented its positioning when it comes to advertising involving children in the role of consumers.